Agricultural industry in West Papua Province: An analysis of backward and forward linkages - Albertus Girik Allo; Marcus R Maspaitella; Sisilia Maria Parinusa; Deasi Mayawati (Agriekonomika, 2022)
Agriculture, Forestry and Fisheries Sector in West Papua Province contributes significantly to the Gross Regional Domestic Product (GRDP). While on the employment side, this sector also able to absorb a third of the workforce in this province. It indicates the important role of this sector in the economy of West Papua Province. The purpose of this paper is to determine the magnitude of the forward and backward linkage of agricultural industry in West Papua Province. The combination of forward and backward linkage will produce a key industry. The Inter-Regional Input Output (IRIO) model and 2016 IRIO data was used in this study. The findings show that Food Crops Agriculture; Annual Horticultural Crops, Annual Horticulture, others; and Livestock is included in the undeveloped category. Meanwhile, Seasonal and Annual Plantations, Forestry and Logging Industries, and Fisheries are in growing industries category. Gross value-added multiplier of all agricultural industries is below one where the highest value is in the Forestry and Logging Industry whereas Livestock Industry is the lowest.